Making It to the School : Education and Transport Policies for Children in South East Europe - World Bank (World Bank, Washington, DC, 2017)
Providing at least basic education to all children especially those coming from poor or disadvantaged families is an important factor for increasing chances to improve their lives in the future. Many countries recognize the need to better educate their populations and do so by trying to improve the equity and quality while taking care of efficiency. The provision of equal educational opportunities is a challenge for every society, where specific solutions typically depend on a number of factors. The intention of this document is to raise awareness and provide support to decision makers in planning the measures that will secure access to quality education for all children above all to those who are under higher risk of dropping out of the education system through a set of transportation and education policy measures. The document aims to equip municipal authorities, as well as transport and education stakeholders, with a systemized approach for assessing the access and accessibility of education services, and tools for the selection of the most appropriate options for improvements. The document is organized as follows: chapter one provides a short introductory review of the demographic changes in South East Europe (SEE) countries; chapter two is a valuable source of information on the experiences of countries in the SEE region and worldwide; chapter three gives decision-making framework for local authorities; chapter four provides a summary and a set of recommendations for local- and national-level authorities on the most effective ways of fulfilling legal obligations and ensuring a basic children's right- access to education; chapter five and six sets paths for making chosen policy options sustainable and for future developments based on innovative transport and education approaches and proven practices; and chapter seven gives literature and data sources.